Effect of Weave Parameters on Thermal Properties of Woven Fabrics. Issue 10 (3rd October 2021) - Prakash, C.; Thanikai Vimal, J.; Jebastin Rajwin, A.; Paranthaman, R.
ABSTRACT: After reviewing the past work into the characterization of weave structures and their relationships with various properties of fabrics, an account is given of the present knowledge of them on comfort properties which represents one of the major areas that have been neglected in garments. The shortcomings of this knowledge are shown to be that, although many studies have been conducted on comfort, there have been no systematic studies of weave structures and their impact on comfort. Thermal comfort properties of fabrics are affected by a gamut of fiber, yarn, and fabric properties. In this study, the characterization in the comfort properties, namely thermal resistance and thermal conductivity, has been studied as a function of weave structures and other geometrical properties.